Fast 3D T2‐weighted imaging using variable flip angle transition into driven equilibrium (3D T2‐TIDE) balanced SSFP for prostate imaging at 3T. Issue 2 (5th September 2014) - Srinivasan, Subashini; Wu, Holden H.; Sung, Kyunghyun; Margolis, Daniel J.A.; Ennis, Daniel B.
<x xml:space="preserve">Abstract</x> Purpose Three‐dimensional (3D) T2‐weighted fast spin echo (FSE) imaging of the prostate currently requires long acquisition times. Our objective was to develop a fast 3D T2‐weighted sequence for prostate imaging at 3T using a variable flip angle transition into driven equilibrium (T2‐TIDE) scheme. Methods 3D T2‐TIDE uses interleaved spiral‐out phase encode ordering to efficiently sample the ky–kz phase encodes and also uses the transient balanced steady‐state free precession signal to acquire the center of k‐space for T2‐weighted imaging. Bloch simulations and images from 10 healthy subjects were acquired to evaluate the performance of 3D T2‐TIDE compared to 3D FSE. Results 3D T2‐TIDE images were acquired in 2:54 minutes compared to 7:02 minutes for 3D FSE with identical imaging parameters. The signal‐to‐noise ratio (SNR) efficiency was significantly higher for 3D T2‐TIDE compared to 3D FSE in nearly all tissues, including periprostatic fat (45 ± 12 vs. 31 ± 7, P < 0.01), gluteal fat (48 ± 8 vs. 41 ± 10, P = 0.12), right peripheral zone (20 ± 4 vs. 16 ± 8, P = 0.12), left peripheral zone (17 ± 2 vs. 12 ± 3, P < 0.01), and anterior fibromuscular stroma (12 ± 4 vs. 4 ± 2, P < 0.01). Conclusion 3D T2‐TIDE images of the prostate can be acquired quickly with SNR efficiency that exceeds that of 3D FSE. Magn Reson Med 74:442–451, 2015. © 2014 Wiley Periodicals, Inc.